Engineering management - Kinsky, Roger (South Melbourne : Thomas Nelson Australia, 1994)
Fundamentals of business. Fundamentals of management. People at work. Self-organising to achieve objectives. Total quality management. Communicating in business. Motivating. Solving problems and resolving conflicts. Occupational health and safety. Managing human resources. Business and the law. Structuring a business. Managing production. Managing finances. Costing and budgeting. Marketing. Purchase and sale by tender.
Keywords: Management; Engineering; Engineering -- Management